Monuments with Early Neolithic Combed Ware from the Southeastern Lake Onega Region - Marina V. Ivanishcheva; Natalya V. Kosorukova (Археология евразийских степей)
The territory of the Southeastern Lake Onega region includes the Southern Lake Onega region, the basins of Lake Beloye and Lake Vozhe within the borders of the Vologda Oblast. Early Neolithic sites with combed ware in this area became known in the late 1980s – early 2000s. Ceramics with combed patterns are the most representative here. At sites, studied on a wide area, radiocarbon determinations were obtained for this group of ceramics, and the composition of the pottery paste was studied. The abundance of material obtained at these sites and its dating by natural science methods make it possible to clarify the chronological position of pottery assemblages of other sites, previously not distinguished from the general array of Neolithic ware and to fill archaeological gaps on the map of Early Neolithic antiquities with factual material. This article provides a review of the ceramic collections of sites with Early Neolithic combed pottery known today in this region.